Should payments for environmental services be used to implement zero-deforestation supply chain policies? The case of soy in the Brazilian Cerrado. (April 2022) - Garrett, R.D.; Grabs, J.; Cammelli, F.; Gollnow, F.; Levy, S.A.
Highlights: Payments for environmental services (PES) have a mixed record on achieving their social and environmental goals. Soy industry actors are considering using PES to end soy-driven deforestation the Brazilian Cerrado. We find that a PES would have a lower likely effectiveness and cost-effectiveness than an MEM, but higher legitimacy among Brazilian soy actors. Both approaches have equity drawbacks – MEM disadvantages soy farmers with forested land and PES unfairly privileges these soy farmers. Mixing an MEM with a PES for only the most vulnerable actors would be a better solution to end deforestation in the Cerrado. Abstract: Over the past decade public and private actors have been developing a variety of new policy approaches for addressing agriculturally-driven deforestation linked to international supply chains. While payments for environmental services (PES) have been advocated in many contexts as an efficient and pro-poor environmental policy to incentivize conservation, they have been the subject of intense scrutiny and criticism for leading to mixed and sometimes adverse environmental and social outcomes. It remains unclear whether such an approach is an improvement over existing approaches to govern sustainability in supply chains and especially as a mechanism for reducing ecosystem conversion. Here we conduct an ex-ante analysis to examine the potential outcomes of using a standalone PES scheme versus existing standalone market exclusion mechanisms (MEM) to govern commodity supply chains. The analysis develops a theoretical framework to examine the potential effectiveness, cost-effectiveness, equity, and legitimacy of the two approaches and then applies this framework using qualitative analysis of secondary and interview data. Using this theory-driven evaluation approach we examine the case of the Brazilian Cerrado, where a PES mechanism is currently being proposed to achieve zero-deforestation targets in soy supply chains. We find that both standalone approaches suffer from different strengths and challenges and would be better used in combination. We conclude that a mixture of strict market exclusion with positive incentives and enabling programs that are targeted at the poorest farmers would be more effective, cost-effective, equitable, and legitimate. However, in the future such supply chain focused soy deforestation control efforts in the Cerrado must be complemented by broader jurisdictional approaches to addressing deforestation and sustainable development that include all land use actors, not just soy farmers. These more inclusive and balanced initiatives can help ensure that avoiding deforestation goes hand in hand with supporting sustainable livelihoods for a wider range of actors in the Cerrado.